Influence of orthodontic treatment with premolar extraction on the spatial position of maxillary third molars in adult patients: a retrospective cohort cone-bean computed tomography study - Fangwei Pan; Zhentao Yang; Jian Wang; Ruilie Cai; Jialing Liu; Chenghao Zhang; Wen Liao (BMC, 2020)
Abstract Background Based on low-dose radiation Cone-bean computed tomography (CBCT) images, This study aims to establish a space coordinate system, which offers more precise and comparable evaluation on changes of maxillary third molars influenced by orthodontic treatment with premolar extraction in adults. The system suggests promising application prospect in future studies related to CBCT superimposition and evaluation for its feasibility and efficiency. Methods Forty-nine maxillary third molars from 27 patients (mean age, 20.78 years) were included. CBCT images were obtained before and after orthodontic treatment with premolars extracted (mean treatment duration, 31.47 months). The changes in the position, angulation, and rotation of the third molars were evaluated with a space coordinate system using four landmarks: anterior nasal spine (ANS), posterior nasal spine (PNS), left and right orbitales. Results After orthodontic treatment, the third molars moved forward (adjusted mean, 1.44 mm) (p < 0.001) and downward (adjusted mean, 2.87 mm) (p < 0.001) accompanied by outward rotation of the crowns (adjusted mean, 5.38°) (p = 0.001), while changes in angulation were insignificant. Conclusions This was the first study to systematically investigate the spatial position change of maxillary third molars in adult patients who received orthodontic treatment with premolar extraction. During the process, maxillary third molars moved downward and forward accompanied by outward rotation of the crowns. Orthodontists should take tooth movement potential into consideration when making extraction plans.